2013
DOI: 10.3389/fnbeh.2013.00027
|View full text |Cite
|
Sign up to set email alerts
|

The Pivotal Role of Semantic Memory in Remembering the Past and Imagining the Future

Abstract: Episodic memory refers to a complex and multifaceted process which enables the retrieval of richly detailed evocative memories from the past. In contrast, semantic memory is conceptualized as the retrieval of general conceptual knowledge divested of a specific spatiotemporal context. The neural substrates of the episodic and semantic memory systems have been dissociated in healthy individuals during functional imaging studies, and in clinical cohorts, leading to the prevailing view that episodic and semantic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
213
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(251 citation statements)
references
References 123 publications
(209 reference statements)
16
213
0
3
Order By: Relevance
“…In relation to future thinking, cognitive neuroscientists and neuropsychologists have generated considerable evidence showing that the capacity to remember past events and imagine future events is closely related, spurring the suggestion that event details can be flexibly extracted and recombined from memory in the service of simulating new events that may take place in the future (20). Here, we extend this proposed relation between memory and future thinking to highlight, as others have done as well (4,11,12,21,22), that general knowledge about the world (semantic knowledge) may also lay the groundwork for allowing us to reason about what the world may be like in the future. However, much work is needed to show these proposed relations between different types of knowledge and future thinking.…”
Section: Modes Of Future Thinking and Types Of Memory Or Knowledgementioning
confidence: 85%
See 1 more Smart Citation
“…In relation to future thinking, cognitive neuroscientists and neuropsychologists have generated considerable evidence showing that the capacity to remember past events and imagine future events is closely related, spurring the suggestion that event details can be flexibly extracted and recombined from memory in the service of simulating new events that may take place in the future (20). Here, we extend this proposed relation between memory and future thinking to highlight, as others have done as well (4,11,12,21,22), that general knowledge about the world (semantic knowledge) may also lay the groundwork for allowing us to reason about what the world may be like in the future. However, much work is needed to show these proposed relations between different types of knowledge and future thinking.…”
Section: Modes Of Future Thinking and Types Of Memory Or Knowledgementioning
confidence: 85%
“…Moreover, it will be important to assess the extent to which these types of knowledge may interact with one another in the service of future-oriented cognition. For example, according to the semantic scaffolding hypothesis (21), semantic knowledge provides a framework or scaffolding that helps to organize event details that comprise simulations of future experiences. This kind of hypothesis implies strong interaction and interdependence between episodic and semantic knowledge during prospective thought (23).…”
Section: Modes Of Future Thinking and Types Of Memory Or Knowledgementioning
confidence: 99%
“…Findings from cognitive, neuropsychological, and neuroimaging research have shown that episodic future thoughts are created based on informational components provided by episodic and semantic memory (i.e., specific past experiences and general knowledge about the world and the self), and multiple cognitive processes are engaged to retrieve, select, and assemble relevant pieces of information (for reviews, see D 'Argembeau, 2015;Irish & Piguet, 2013;Klein, 2013;Schacter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To anticipate our conclusions, we argue that although there is a marked tendency to treat FMTT as a unitary mental faculty that, despite task-driven outward variation, ultimately reduces to a common phenomenological state (underwritten primarily by episodic memory), FMTT is neither unitary nor is it necessarily beholden to episodic memory (on this latter point, see also Abraham & Bubic, 2015;Irish, Chapter 19 of this volume;Irish & Piguet, 2013;and Klein, 2103a). Rather, FMTT is diverse both in its experiential realizations and causal dependencies.…”
Section: Goals Of the Ch Aptermentioning
confidence: 99%